Easy Rests the Head - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses how to determine a harmonious color scheme when redecorating a bedroom. Describes several bedroom design schemes for inspiration. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Interior decoration; Paint materials; Bedrooms--Remodeling; Color in interior decoration; Varnish and varnishing; Dwellings--Remodeling; Paint industry and trade; Advertising--Paint